The study of effective factors on some of the biologic rhythms from the view point of hospitalized patients - SH Najafi Doulatabad; A Najafi Doulatabad; SJ Sadat; Z Mohebbi Nobandegani (Occupational Health and Safety Society of Nepal, 2011)
Many human vital actions like sleep and waken, defecation, blood pressure, body temperature, etc. are being done as rhythmic. The factors on these rhythms among hospitalized patients in the hospitals can outshine the patients recovery and hospitalization period so, the present research has been performed with the aim to study of the effective factors on some biological rhythms from point of view of hospitalized patients at medical ward of the Emam Sajad hospi tal of Yasouj city 2008-2009. This research is a descriptive sectional study, performed on hospitalized patients at medical wards of hospitals of Yasouj city during the years 2008-2009. Sampling method was as purposive accessible sampling and the numbers of samples were 100.0 persons. The data collection tool was questionnaire. Collected data were analyzed using SPSS software and descriptive statistical tests. 68.0% and 83.0% of samples were suffering from sleep reduction and anorexia respectively. 61.0% of samples also mentioned some change in their defecation. Among environmental factors, noise in the ward with 65.0%, among personal factors, anxiety regarding recovery and obtaining health with 60.0% and among caring factors, having serum and keep awake to receive medicine with 57.1% have been effective on the sleep reduction of patients with the rates of very much and much. Regarding the effective factors on appetite reduction of patients, smelly environment and undesir able food with 21.0% each, were among the most influential factors. Regarding the effective factors on defecation reduc tion also lack of activity with 25.5% had the maximum role. Since the most important effective factors in biologic rhythms which are under studying are adjustable and it is possible to remove them therefore, it is necessary for the caring personnel to prepare the rest possibility and comforta bility of patients in desirable manner by more accuracy and removing such factors and giving education to the patients,